Dietary Patterns and Fitness Level in Mexican Teenagers - César Estrada-Reyes; Patricia Tlatempa-Sotelo; Roxana Valdés-Ramos; María Cabañas-Armesilla; Rafael Manjarrez-Montes-de-Oca (Journal of Nutrition and Metabolism)
Background. Nowadays, the term “physical fitness” has evolved from sports performance to health status, and it has been considered a strong predictor of cardiovascular disease. In this sense, test batteries have been developed to evaluate physical fitness such as the ALPHA-FIT battery. On the other hand, the analysis of dietary patterns has emerged as an alternative method to study the relationship between diet and chronic noncommunicable diseases. However, the association between dietary patterns and the physical fitness level has not been evaluated in both adults and adolescents. This association is most important in adolescents due to the fact that establishing healthy dietary behaviors and a favorable nutritional profile in early stages of life prevents various chronic-degenerative diseases. Objective. To analyze the association between dietary patterns and the level of fitness in Mexican teenagers. Methods. We analyzed the relationship between dietary patterns and the fitness level of 42 teenage students in Toluca, Mexico. Students were weighed and measured, and their food intake was recorded for 2 weekdays and one weekend day. Dietary patterns were obtained by factorial analysis. The ALPHA-FIT battery was used to measure the fitness level. Results. Fifty percent of the students were found to have a low fitness level (62.1% men; 37.9% women). There was no association (X2 = 0.83) between the dietary patterns “high in fat and sugar,” “high in protein”, and “low in fat and protein” and the level of physical condition in teens. Conclusions. In this study, all of teenagers with a very low level of fitness obtained a high dietary pattern in protein; however, 40% with a high level of physical condition resulted in the same pattern; that is why we did not find a relationship between the fitness level and the patterns investigated in this study.